PENERAPAN DOKTRIN ULTRA VIRES DALAM KASUS PRODUKSI DAN DISTRIBUSI GARAM (STUDI PT SUMATRACO LANGGENG MAKMUR SURABAYA): The Application Of Ultra Vires Doctrine In Salt Production And Distribution Cases (Study Pt Sumatraco Langgeng Makmur Surabaya) - Rais Zaidan Rizqullah; Sri Bakti Yunari (AMICUS CURIAE, 2025)
The main company organ in managing the company is the board of directors. The board of directors has the responsibility to manage the company in the interests of the company as regulated in Article 92 of Law Number 40 of 2007. The problem are regarding the application of the Ultra Vires doctrine in the case of the production and distribution of PT Sumatraco Langgeng Makmur salt as well as regarding the responsibilities of the directors in the case PT Sumatraco Langgeng Makmur salt production and distribution based on concerning Limited Liability Companies. The research method was carried out with a normative juridical type, descriptive in nature, using secondary data, analyzed qualitatively and concluded using a deductive method. The result research and conclusion is, application of the ultra vires doctrine in this case is related to the proven actions taken by the directors exceeding and outside their authority in Article 3 of the company's articles of association in clause on company's aims and objectives and contrary to Article 92 of Law Number 40 of 2007. As an alternative step, shareholders can use Article 61 of concerning Limited Liability Companies to file a civil  if they feel disadvantaged by decision of GMS, Directors or Board of Commissioners.